Utilização de tubos geotêxteis para confinamento, desaguamento e empilhamento de rejeito de ouro - Lais Cristina Freitas Silva (2017)
The use of non-traditional methods to dispose mine tailings, such as geotextile tubes, has several advantages. For instance, it is possible to decrease risks regarding failure probability as well as to reduce the necessary area to dispose tailings. If damage associated with a possible structural failure is considerably minimized, then the relationship among mining companies, communities, and environment is more sustainable. Also, it helps to raise awareness about these aspects concerning mineral extraction. Therefore, geotextile tubes is an available engineering technique to dispose gold tailings; once the tube is permeable, it allows the excess water to pass through the geotextile skin while the retained tailings attains a compact and stable mass within the tube. The study aims to present the field experience on using woven geotextile tubes as an alternative on dewatering, confining and also to construct an engineering structure by stacking tubes. This research project covered several laboratory tests to characterize both gold ore tailings and the woven-geotextile used to manufacture the tubes. Tests to evaluate dewatering efficiency were also conducted in laboratory. Cycloned gold tailings came from a specific mining area where a large scale prototype was developed at. Gold ore tailings were submitted to geotechnical and hydraulic laboratory tests, such as specific weight measurement, particle-size analysis by sieving and sedimentation, consistency limits, and hydraulic consolidation test. Also, woven-geotextile used to fabricate tubes had its mass per unite area and thickness measured in laboratory. Dewatering efficiency was evaluated by means of jar-test, geotextile cone test, and geotextile dewatering test (GDT) which utilizes a pillow-shaped bag that allows dewatering in all directions. The large scaleprototype was installed at the field when laboratory tests were finished. Important project variables were then evaluated: time required to fill geotextile tubes as a function of pumped volume; observed changes in shape and behavior of tubes when its width and height varied along the filling process; design aspects of pumping and stacking; dewatered fluid characteristics; deformation and settlement of individual geotextile tubes and during the process of stacking tubes. Likewise, field tests were important to analyze external limit state modes, specially the one in regards to sliding stability, when tubes start to roll. Both laboratory and field tests results have shown a good performance for the technique. Almost all free water was allowed to flow out of the geotextile tubes over the filling process. It was observed a solid content greater than 70% when dewatering was completed. Data collected at the field was used to estimate internal stresses developed at the geotextile tube from formulations that relate stresses at tubes fabric to tubes geometric parameters, as height, width, diameter and perimeter